2015
DOI: 10.21608/avmj.2015.170208
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Oxidative Status, Milk Quality and Conception Rate in Dairy Goats Supplemented With Vitamin C

Abstract: Pregnant Agamy does were used in this experiment to evaluate the effects of Vitamin C (Vit C) supplementation as antioxidant agent to improve the performance of dairy goats during the evidence of oxidative stress (OS) in peri-parturient period. The does under experiment (n = 16) were assigned randomly into control and supplemented groups (n = 8 / group). The control group fed control diet without supplement and the supplemented group fed control diet plus Vit C 75mg/kg of body weight. Dietary supplementation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The findings of present study agree with that of Ognik et al (2015) who had reported that there was no change in Vitamin C concentration during various stages of lactation. Howida et al (2015) concluded that vitamin C supplementation enhanced to the adverse effects of oxidative stress and improved milk quality. The reason for low T 3 and T 4 could be breakdown of fat and protein in mammary tissue (Riis and Madsen, 1985).…”
Section: Results For Mean ± Se In Lohi Sheep and Beetal Goats During ...mentioning
confidence: 99%
“…The findings of present study agree with that of Ognik et al (2015) who had reported that there was no change in Vitamin C concentration during various stages of lactation. Howida et al (2015) concluded that vitamin C supplementation enhanced to the adverse effects of oxidative stress and improved milk quality. The reason for low T 3 and T 4 could be breakdown of fat and protein in mammary tissue (Riis and Madsen, 1985).…”
Section: Results For Mean ± Se In Lohi Sheep and Beetal Goats During ...mentioning
confidence: 99%